INTELLIGENT APPLICATION OF DIGITAL SHARED MANAGEMENT SYSTEM IN JOURNAL RESOURCE INTEGRATION - Cai, Yong (3C TIC, 2024)
In this paper, a journal resource integration system under digital sharing was designed to assess the symmetry of the journal resource matrix using the shared resource matrix analysis method, so that the journal resources can transmit information covertly among the subjects. Subsequently, the collected journal resource data were processed to improve the accuracy of information categorization and integration to form a perfect resource management system. The nature of journal resources was deeply understood by calculating the characteristic observable vectors of journal resources. Finally, with the help of ant colony particle optimization algorithm, the sharing sequence and time of journal resources were calculated, and the metadata format of all journals was unified and standardized to complete the design of journal resource integration system. The results show that the whole average integration efficiency of journal resources is 92.8%. Compared with the traditional integration system, the integration efficiency is improved by 28.3%, which fully confirms the significant performance improvement of the designed digital system in the integration of shared journal resources.